(untitled) (Vietnam Journal of Community Medicine, 2020)
Research on the satisfaction of 260 outpatient patients at Tieu Can general hospital. Methodology: Cross-sectional studies. Interview the subjects with the hospital quality assessment toolkit of the MOH. Results: The results show that, an accessibility satisfaction was 41.9%. Transparency of information and medical examination and treatment procedures reached 47.7%, facilities and equipments for patients reached 58.1%. Satisfaction, behavioral attitude, professional capacity of health workers reached the rate of 33.1%, satisfaction with the quality results of service delivery 37.3%. Conclusion: Patient satisfaction on outpatient care is relatively low.